2017
DOI: 10.1002/ajp.22639
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in zoo‐housed squirrel monkeys' (Saimiri sciureus) reactions to visitors, research participation, and personality ratings

Abstract: Understanding individual differences in captive squirrel monkeys is a topic of importance both for improving welfare by catering to individual needs, and for better understanding the results and implications of behavioral research. In this study, 23 squirrel monkeys (Saimiri sciureus), housed in an environment that is both a zoo enclosure and research facility, were assessed for (i) the time they spent by an observation window under three visitor conditions: no visitors, small groups, and large groups; (ii) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…Previous studies have demonstrated that individuals can vary in their behavioral responses [ 21 , 51 , 52 ]. We found further evidence that individual animals of the same species in the same exhibit do not always respond in the same manner to humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that individuals can vary in their behavioral responses [ 21 , 51 , 52 ]. We found further evidence that individual animals of the same species in the same exhibit do not always respond in the same manner to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Individual animals can vary in their responses to zoo visitors [ 21 , 51 , 52 ]. A study of three polar bears ( Ursus maritimus ) found one animal increased and two animals decreased stereotypical behavior during periods of higher visitor density [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also likely that there are individual differences contributing to the results obtained here, and teasing out how personality or temperament influences responses to social stimuli is an important future direction. Related, there may have been selfselection among the subjects in that the subset of touchscreen trained animals who voluntarily participated during the Air and Water Show may have been willing to do so because they experienced less stress than groupmates (see Morton, Lee, & Buchanan-Smith, 2013;Polgar, Wood, & Haskell, 2017). However, that would have led us to underestimate the impact on mood for Japanese macaques.…”
Section: Discussionmentioning
confidence: 99%
“… Self-selected participation in experiments was correlated with personality traits in squirrel monkeys 36 .…”
Section: The Authorsmentioning
confidence: 99%